2010
DOI: 10.1108/14757701011019790
|View full text |Cite
|
Sign up to set email alerts
|

Continuous auditing for web‐released financial information

Abstract: PurposeThe increasing provision of timely financial information through web‐based technology is expected to improve the quality of communication between a company and its stakeholders. However, the information asymmetry problem still exists since almost all “web‐releases” usually remain unaudited. The purpose of this paper is to propose conceptual and technical frameworks of continuous auditing to provide a solution for this problem. This solution could also move the traditional auditing forward to the new e‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…However, inevitably many of the risks, controls and testing procedures will significantly change with the introduction of e‐business (Arens & Loebbecke, 1976; APB, 2001; Glover et al ., 2001; Moscove et al ., 2003; Abu‐Musa, 2004; Hunton et al ., 2004; Chou & Chang, 2010). For example:…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, inevitably many of the risks, controls and testing procedures will significantly change with the introduction of e‐business (Arens & Loebbecke, 1976; APB, 2001; Glover et al ., 2001; Moscove et al ., 2003; Abu‐Musa, 2004; Hunton et al ., 2004; Chou & Chang, 2010). For example:…”
Section: Resultsmentioning
confidence: 99%
“…These findings echo those reported in Table 8, where more than half of the respondents indicated that they thought audit timing would not significantly change in response to e‐business (52.2 per cent report 1 or 2, mean 2.48). Thus, many of the respondents appear not to agree with the literature which stresses the importance of real‐time auditing techniques (see, for example, Helms & Mancino, 1998; Cosserat, 2004; Hunton et al ., 2004; Chou & Chang, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations